Dissection of Barley Landraces Originated From Twelve Different Countries by Using Simple Sequence Repeats Markers - (:unkn) unknown (ANKARA UNIV, FAC AGR, 2015)
Landraces, as an important source of genetic diversity, are important for improvement of crop species. Investigating of genetic diversity among landraces is necessary to conserve genetic resources and develop future strategies on barley breeding. In this study, genetic diversity in barley landraces originating from twelve countries was studied using simple sequence repeat (SSR) markers. Sixteen SSR markers belong to the seven barley linkage groups revealed high genetic diversity. A total of 92 polymorphic alleles were scored and the number of alleles ranged from 1 to 7 per locus, with an average of 5.75. Genetic diversity was the highest in landraces from Turkey (0.66 +/- 0.13) and the lowest in those from Ukraine (0.38 +/- 0.24). While the highest percentage of polymorphic loci was found for landraces from Germany, Netherland, Russia, Turkey and USA as 100%, the lowest one was in England with 75%. Clustering analysis of landraces divided them into four main groups. The results provided additional genetic information about the barley landraces from different countries for future breeding process.
Keywords: Barley; Landraces; SSRs; Diversity; GENETIC DIVERSITY; SSR; MICROSATELLITES; IDENTIFICATION; WILD